(untitled) (Research, Society and Development, 2025)
Fibro-osseous lesions are conditions that can affect the gnathic bones, being classified into fibrous dysplasia, ossifying fibroma and cemento-osseous dysplasia. In general, it comprises several lesions where normal bone tissue is replaced by collagen fibers and fibrous tissue, containing considerable mineralized substance that may have a bone or cementoid appearance. Fibrous dysplasia is more common in the first two decades of life and affects women more than men. The diagnosis is made through the association of symptoms with imaging tests, but biopsy is necessary for confirmation. The present work proposes to report a case of a 20-year-old female patient, presenting characteristics of fibrous dysplasia and ossifying fibroma who underwent treatment of lesion resection and reconstruction of the area with xenogenous bone graft. An assertive and accurate diagnosis of these injuries is essential for the patient’s prognosis and the success of the treatment.